2015
DOI: 10.1038/srep07642
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of the hydrolysis of the endocannabinoid 2-arachidonoylglycerol impairs learning and memory performance while producing antinociceptive activity in rodents

Abstract: Monoacylglycerol lipase (MAGL) represents a primary degradation enzyme of the endogenous cannabinoid (eCB), 2-arachidonoyglycerol (2-AG). This study reports a potent covalent MAGL inhibitor, SAR127303. The compound behaves as a selective and competitive inhibitor of mouse and human MAGL, which potently elevates hippocampal levels of 2-AG in mice. In vivo, SAR127303 produces antinociceptive effects in assays of inflammatory and visceral pain. In addition, the drug alters learning performance in several assays r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 73 publications
5
105
1
Order By: Relevance
“…Interestingly, compound 157-induced analgesic effects can be reversed by a CB1 (131) but not a CB2 (1) antagonist, which indicated that 157 mainly produced analgesia through a CB1-dependent mechanism. 169 Although the administration of 157 was demonstrated to be devoid of inducing hypothermia, catalepsy, and hypomotility, it resulted in an alteration of learning and memory performance. This adverse property might limit the application of 157 in a clinical setting.…”
Section: Carbamatesmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, compound 157-induced analgesic effects can be reversed by a CB1 (131) but not a CB2 (1) antagonist, which indicated that 157 mainly produced analgesia through a CB1-dependent mechanism. 169 Although the administration of 157 was demonstrated to be devoid of inducing hypothermia, catalepsy, and hypomotility, it resulted in an alteration of learning and memory performance. This adverse property might limit the application of 157 in a clinical setting.…”
Section: Carbamatesmentioning
confidence: 99%
“…This adverse property might limit the application of 157 in a clinical setting. 169 The investigation of its binding mechanism indicated that the Ser132 of MAGL could interact with the carbamate moiety of 157 accompanied by the release of hexafluoropropyloxy group. The carbonyl oxygen of the carbamate moiety was suggested to serve as an H-bond acceptor and bind to Ala61/Met133.…”
Section: Carbamatesmentioning
confidence: 99%
See 3 more Smart Citations